DESIGN TOOLS TO SAFE GUARD DISTANCE four wheel drive microcontroller AT89S51 - Indrianto Indrianto (JAKSTIK Journal, 2006)
Designing tools to guard the safe distance of the automobile-based Microcontroller AT89S51 intended to reduce the number of accidents particularly for four-wheeled vehicle that almost happen every day either street or highway within the highway. This happens because not all vehicles have a range of security system that serves as a critical distance when the distance a vehicle warner they are too close to another vehicle. Equipment will be placed on front bumper which gives a warning if the distance is too close. With hopes of vehicle accidents can be avoided.